2012
DOI: 10.1245/s10434-011-2201-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of ABCB6 Enhances Protoporphyrin IX Accumulation and Photodynamic Effect in Human Glioma

Abstract: Our findings indicate a crucial role of ABCB6 in ALA metabolism and accumulation of PpIX in glioma. ABCB6 overexpression is a potential approach to enhance accumulation of PpIX for optimizing the subjective discrimination of vague fluorescence and improving the efficacy of ALA-based photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 34 publications
2
65
0
1
Order By: Relevance
“…Therefore, ABCB6 was thought to be primarily involved in the transporting coproporphyrin III into the mitochondria for PpIX/heme b synthesis (79). Increased ABCB6 expression has been linked to an increase in fluorescence in human glioma tissues allowing for better contrast in fluorescence-guided surgery, via more sufficient PpIX accumulation (80). ABCB6 is located in the cell membrane and Golgi apparatus, and transports coproporphyrinogen III between the cellular departments (8183).…”
Section: ‘Pro-dye’ Fluorescent Agent 5-alamentioning
confidence: 99%
“…Therefore, ABCB6 was thought to be primarily involved in the transporting coproporphyrin III into the mitochondria for PpIX/heme b synthesis (79). Increased ABCB6 expression has been linked to an increase in fluorescence in human glioma tissues allowing for better contrast in fluorescence-guided surgery, via more sufficient PpIX accumulation (80). ABCB6 is located in the cell membrane and Golgi apparatus, and transports coproporphyrinogen III between the cellular departments (8183).…”
Section: ‘Pro-dye’ Fluorescent Agent 5-alamentioning
confidence: 99%
“…activity towards porphyrins impacts heme metabolism [29], hematopoiesis [30], photodynamic therapy [31] and parasite killing in macrophages [32]. Therefore, a heterologous expression system with correctly folded human ABCB6 expressed in a eukaryotic host with glycosylation patterns and membrane lipid composition similar to mammalian ones would greatly help the complicated task of unraveling the molecular questions of ABCB6 biochemistry.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Glioma tissue was intraoperatively characterized by strong PpIX fluorescence, whereas normal tissue revealed no visible PpIX. A more recent study demonstrated that the accumulation of 5-ALA-mediated PpIX in glioma cells is enhanced by increased expression of the ABC mitochondrial porphyrin importer ABCB6, and that ABCB6 expression was greatly elevated in human gliomas compared with normal brain tissue (118).…”
Section: Intraoperative Imaging Of Tumors or Their Metastasesmentioning
confidence: 99%